ENCRYPTION AND DATA INSERTION TECHNIQUE USING REGION DIVISION AND HISTOGRAM MANIPULATION - Ito, Ryoma; Wong, KokSheik; Ong, Simying; Tanaka, Kiyoshi (Malaysian Journal of Computer Science, 2021)
Traditionally, encryption is applied to mask the semantic of a content, while data insertion adds data to a content for management purpose. In this work, a joint encryption and data insertion method is proposed. The input image is divided into 2 parts, where the first part is manipulated to mask the perceptual semantics, while the second part is processed to hide data. The binary image, which is the data to be inserted, further divides the second part of the input image into 2 regions, one being the ‘zero’ region and the other being the ‘one’ region. Pixels of the original image at position coinciding with the ‘zero’ region are darken, while those coinciding with the ‘one’ region are brightened. The darkening and brightening processes are performed by using histogram matching technique. Furthermore, two techniques are introduced to improve robustness of the inserted binary image against basic image processing operations. The proposed joint method allows the inserted binary image to be extracted directly from the masked image or from the reconstructed image. The proposed method is also commutative because the same result is achieved irregardless of the order of processing in encrypting and inserting data.